Lunar and Planetary Science XVIII : abstracts of papers submitted to the eighteenth Lunar and Planetary Science Conference, March 16-20, 1986 (Lunar and Planetary Institute, 1987)
You must extract the zipped files before using. To begin viewing the abstracts, click on the file "index.html." Papers on lunar and planetary science are presented, including petrogenesis and chemistry of lunar samples, geology and petrogenesis of the Apollo 15 landing site, lunar geology and applications, cratering records and cratering effects, differentiated meteorites, chondritic meteorites and asteroids, extraterrestrial grains, Venus, Mars, and icy satellites. The importance of lunar granite and KREEP in very high potassium basalt petrogenesis, identifying parent plutonic rocks from lunar breccia and soil fragments, glasses in ancient and young Apollo 16 regolith breccias, the formation of the Imbrium basin, the chemistry and petrology of the Apennine Front, lunar mare ridges, studies of Rima Mozart, electromagnetic energy applications in lunar resource mining and construction, detecting a periodic signal in the terrestrial cratering record, and a search for water on the moon, are among the topics discussed. Other topics include the bidirectional reflectance properties of Fe-Ni meteorites, the nature and origin of C-rich ordinary chondrites and chondritic clasts, the dehydration kinetics of shocked serpentine, characteristics of Greenland Fe/Ni cosmic grains, electron microscopy of a hydrated interplanetary dust particle, trapping Ne, Ar, Kr, and Xe in Si2O3 smokes, gossans on Mars, and a model of the porous structure of icy satellites. sponsored by Lunar and Planetary Institute . [and others] PARTIAL CONTENTS: Quantitative Evaluation of Ballistic Sedimentation / Sullivan, R. -- The Lunar Geoscience Observers Role in Unraveling the Magmatic Evolution of the Moon / Taylor, G.J. -- Loss of Volatile Elements During Impact Events in Relation to Lunar Composition and Origin / Taylor, S.R. -- Limb Topography of Uranian Satellites / Thomas, P. -- Goldstone Radar Observations of Mars: The 1986 Opposition / Thompson, T.W.